Exploring the Impact of Instagram Use on Adolescents' Global Diversity Values: A Case Study of Toxic Relationship in Narcissistic Personality Disorder (NPD) - Irma Meidiana Kusumaningtyas; Ambiro Puji Asmaroini; Sunarto Sunarto; Singkir Hudijono (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study investigates the impact of Instagram use on adolescents' global diversity values, particularly in the context of toxic relationships exacerbated by Narcissistic Personality Disorder (NPD) traits. A quantitative, cross-sectional survey was conducted with 100 respondents from SMKN 1 Ponorogo and Muhammadiyah Ponorogo University. Data were collected using a questionnaire measuring Instagram use, global diversity values, toxic relationship intensity, and narcissistic tendencies. Analysis included validity, reliability, and T-tests using SPSS software. The findings revealed that Instagram use significantly influences adolescents' global diversity values through an "echo chamber" effect, which reinforces pre-existing beliefs and limits exposure to diverse perspectives. Additionally, toxic relationships, characterized by NPD traits such as a need for excessive validation and emotional manipulation, negatively impact adolescents' attitudes toward cultural and social differences. These results highlight the complex interplay between social media use, mental health, and adolescents’ global outlook. Instagram's reinforcement of biased perspectives and the prevalence of toxic relationship dynamics underscore the need for targeted interventions. The study emphasizes the importance of promoting social media literacy, education on healthy relationships, and mental health support for adolescents. These insights are critical for educators, parents, and policymakers to design strategies that mitigate the adverse effects of social media on adolescents' global diversity values and interpersonal relationships. Further research should explore longitudinal impacts and intervention efficacy.